Lucky eaudiobook - Stapley, Marissa (Simon & Schuster, 2021)
REESE'S BOOK CLUB PICK NEW YORK TIMES BESTSELLER A thrilling roller-coaster ride about a heist gone terribly wrong, with a plucky protagonist who will win readers' hearts. What if you had the winning ticket that would change your life forever, but you couldn't cash it in? Lucky Armstrong is a tough, talented grifter who has just pulled off a million-dollar heist with her boyfriend, Cary. She's ready to start a brand-new life, with a new identity—when things go sideways. Lucky finds herself alone for the first time, navigating the world without the help of either her father or her boyfriend, the two figures from whom she's learned the art of the scam. When she discovers that a lottery ticket she bought on a whim is worth millions, her elation is tempered by one big problem: cashing in the winning ticket means she'll be arrested for her crimes. She'll go to prison, with no chance to redeem her fortune. As Lucky tries to avoid capture and make a future for herself, she must confront her past by reconciling with her father; finding her mother, who abandoned her when she was just a baby; and coming to terms with the man she thought she loved—whose dark past is catching up with her, too. This is a novel about truth, personal redemption, and the complexity of being good. It introduces a singularly gifted, multilayered character who must learn what it means to be independent and honest...before her luck runs out.